The Nexus Between the Big Five Personality Traits Model of the Digital Economy and Blockchain Technology Influencing Organization Psychology - Dan, Yu; Ahmed, Alim Al Ayub; Chupradit, Supat; Chupradit, Priyanut Wutti; Nassani, Abdelmohsen A.; Haffar, Mohamed (Frontiers in Psychology, 2021)
To increase emotional intelligence, the Big five digital economy model and use of block chain technology is quite important. The link between the digital economy characteristics and emotional intelligence in term of blockchain technology among Chinese workers is investigated in this study. The theoretical underpinning for the study's research model was also supplied by this research. Deductive reasoning is used in this study, and positivism is the overarching philosophy. The PLS-SEM estimation methodology was used in this investigation. Convenience sampling was used and a total of 260 respondents was considered for the analysis. This approach consists of two stages: measurement model evaluation and structural model evaluation. The measurement model demonstrated that all items and constructs are valid and reliable for measuring all of the model's components. Following that, the structural model evaluation indicated that four of the five hypotheses are accepted. In summary, this study found that block chain technology accurately predicts emotional intelligence among Chinese employees. These findings are critical for human resource specialists and other top management stakeholders to comprehend the behavior of employees in term of perusing the block chain technology.